2016
DOI: 10.3390/v8120322
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine, an Endocytosis Blocking Agent, Inhibits Zika Virus Infection in Different Cell Models

Abstract: Zika virus (ZIKV) infection in utero might lead to microcephaly and other congenital defects. Since no specific therapy is available thus far, there is an urgent need for the discovery of agents capable of inhibiting its viral replication and deleterious effects. Chloroquine is widely used as an antimalarial drug, anti-inflammatory agent, and it also shows antiviral activity against several viruses. Here we show that chloroquine exhibits antiviral activity against ZIKV in Vero cells, human brain microvascular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
201
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(217 citation statements)
references
References 56 publications
8
201
0
5
Order By: Relevance
“…Chloroquine has been shown to reduce the number of ZIKV-infected cells in vitro, and inhibit virus production and cell death promoted by ZIKV infection without cytotoxic effects. In addition, chloroquine treatment partially reverses morphological changes induced by ZIKV infection in mouse neurospheres [52].…”
Section: Chloroquinementioning
confidence: 93%
See 2 more Smart Citations
“…Chloroquine has been shown to reduce the number of ZIKV-infected cells in vitro, and inhibit virus production and cell death promoted by ZIKV infection without cytotoxic effects. In addition, chloroquine treatment partially reverses morphological changes induced by ZIKV infection in mouse neurospheres [52].…”
Section: Chloroquinementioning
confidence: 93%
“…ZIKV pass through endosomes; since the subsequent acidification is essential for exiting the endosomes [51], chloroquine and hydroxychloroquine could trap viral particles thus preventing their escape. Studies demonstrate a strong reduction in the release of ZIKV particles when the drug was added at 0 h post-infection, suggesting a higher impact on early stages of infection, possibly during fusion of the envelope protein to the endosome membrane [52]. Furthermore, it has recently been shown that chloroquine exhibits antiviral activity against ZIKV in Vero cells, human brain microvascular endothelial cells, and human neural stem cells [52].…”
Section: Chloroquinementioning
confidence: 99%
See 1 more Smart Citation
“…This drug has been described to exhibit anti-ZIKV activity in Vero cells (44). The agent also affected ZIKV-infected hBMECs, as well as human NSCs, for which the depletion of is one of the main mechanisms responsible for primary microcephaly (45).…”
Section: Host-targeting Antiviralsmentioning
confidence: 99%
“…The agent also affected ZIKV-infected hBMECs, as well as human NSCs, for which the depletion of is one of the main mechanisms responsible for primary microcephaly (45). Chloroquine reduced the number of ZIKV-infected cells, thereby inhibiting virus production (including of defective viral particles), and reduced cell death promoted by ZIKV infection, thus interfering with the early stages of the ZIKV replication cycle, possibly during the fusion of the envelope protein to the endosomal membrane (44). The reported EC 50 s were 9.8 M, 14.2 M, and 12.3 M (for therapeutic indexes [TIs] of 13.7, 8.2, and 7.7) for Vero, hBMECs, and NSCs, respectively.…”
Section: Host-targeting Antiviralsmentioning
confidence: 99%